Fibromyalgia associated with repeated gadolinium contrast-enhanced MRI examinations - Silvia Maria Lattanzio, PhD; Francesca Imbesi, MD (Radiology Case Reports, 2020)
We report a case of a fibromyalgia (FM) patient with an history of brain-cancer presenting signs and symptoms of gadolinium toxicity following repeated administrations of a macrocyclic contrast agent, Gadovist. In the present report, we provide evidence supporting the hypothesis of a causal relationship linking gadolinium deposition to a clinical manifestation of disease, namely fibromyalgia. We unravel a role for gadolinium in the still unknown etiology of fibromyalgia as a metal toxicity disorder. Contrast agents are routinely administered in a clinical context. It is thus possible that the patients are mistakenly believed to show complaint of their primary disease, whereas, in some instances, their symptoms are associated with gadolinium deposition. Keywords: Gadolinium deposition, Fibromyalgia syndrome, Chronic pain, Toxicity, Contrast agents, Magnetic resonance imaging